Structuring an interactive guide on recommendations for safe and early dental care for patients with dementia (Research, Society and Development, 2022)
Considering the need to expand the reach of health education for the population affected by dementia, an educational product of easy dissemination was created, an interactive tutorial guide, entitled “Oral health practices in elderly people with dementia” that sought to incorporate the technology to facilitate the teaching-learning process. It was structured based on the CTM3 method where they are didactically grouped into stages and based on three theories, Product Design, Theoretical Framework and Methodological Framework. The theoretical framework covers the theoretical foundation on the subject and type of product to be developed, demonstrates its relevance and usefulness and underpins its design. The elaboration of the educational product followed the following steps: conception of the idea, choice of the target audience, establishment of the objective, and establishment of the budget. Then, the steps and topics to be addressed, text structure, as well as definition of videos to be included and articles to support the exposed theme were defined. The content explored was based on the scientific literature related to oral health care and practices used in elderly people with dementia. The product was validated by a master's defense committee, with no suggestions to change its original format, where the validated opinion was issued without changes, the final version was published on the EduCAPES Portal. This educational product proposal presents instruments that seek to facilitate the teaching-learning process, through the establishment of educational practices, instructing caregivers and dentists about oral health practices in patients with dementia using technology as a moderator of the process.